Vacina terapêutica: avaliação de Mycobacterium bovis BCG recombinante para imunoterapia de câncer superficial de bexiga - Begnini, Karine Rech (2012)
Bacillus Calmette-Guerin (BCG) is one of the great success stories of immunotherapy as a treatment for superficial urothelial carcinoma of the bladder. The high incidence of local side effects and presence of non-responder diseases has led to efforts to improve the therapeutic vaccine. Hence, we proposed that an auxotrophic recombinant BCG strain overexpressing Ag85B (BCG ΔleuD/Ag85B), could enhance cytotoxicity to the human bladder carcinoma cell line (5637). This rBCG was generated by incorporating an expression plasmid encoding the mycobacterial antigen Ag85B into the BCG ΔleuD strain. The inhibitory effect of BCG ΔleuD/Ag85B in 5637 cells was determined by the MTT method, morphology observation and the LIVE/DEAD assay. Gene expression profiles for apoptotic genes, cell cycle-related genes and oxidative stress-related genes were investigated by qRT-PCR. Bax, bcl-2 and p53 induction by BCG ΔleuD/Ag85B treatment were evaluated by Western blotting. BCG ΔleuD/Ag85B revealed a superior cytotoxicity effect than the strains used as controls in this study. The results demonstrated that the expression level of pro-apoptotic and cell cycle-related genes increased after BCG ΔleuD/Ag85B treatment, whereas mRNA levels of antiapoptotic genes decreased. Interestingly, BCG ΔleuD/Ag85B also increased the mRNA level of antioxidant enzymes in bladder cancer cell line. Bax and p53 protein levels were increased by BCG ΔleuD/Ag85B treatment. In conclusion, these results suggested that BCG ΔleuD/Ag85B enhanced cytotoxicity on superficial bladder cancer cells in vitro. The therapeutic model using rBCG may have potential for future clinical application in the treatment of bladder cancer.